Alien species on the coasts of Turkey - CINAR, M.E.; BILECENOGLU, M.; OZTURK, B.; KATAGAN, T.; AYSEL, V. (Mediterranean Marine Science, 2005)
The compilation of data on alien species reported from the Turkish coasts yielded a total of 263 species belonging to 11 systematic groups, of which Mollusca had the highest number of species (85 species), followed by Crustacea (51), fishes (43) and phytobenthos (39). The Black Sea is represented by a total of 20 alien species, the Sea of Marmara by 48 species, the Aegean Sea by 98 species and the Levantine Sea by 202 species. The majority of aliens found in the Black Sea and the Sea of Marmara were transported via shipping, whereas the Levantine coast is extensively subjected to Lessepsian migration. Benthic habitats (soft and hard substrata) comprise 76% of the total alien species and the pelagic environment is inhabited by thirty-nine species. Almost 50% of aliens collected from the Turkish coasts were found only at 0-10 m depth. Eight species occur at depths deeper than 100 m. The impacts of aliens on the benthic and pelagic ecosystems are presented.